Pulitzer : a life in politics, print, and power - Morris, James McGrath (New York : Harper, 2010)
Like Alfred Nobel, Joseph Pulitzer is better known today for the prize that bears his name than his contribution to history. Yet, in 19th-century industrial America, Pulitzer invented the modern mass media. Morris offers the definitive biography of this remarkable icon
Includes bibliographical references (p. [531]-536) and index.
Keywords: Pulitzer, Joseph, 1847-1911.; Journalists -- United States -- Biography